Vasorelaxant Effects of Ethanolic Extract from Cydonia oblonga Mill. Leaves on Isolated Rat Thoracic Aorta and Potential Mechanism of Action - Krasniqi, Donjeta; Uka, Albina; Rexhbeqaj, Era; Beretta, Giangiacomo; Petreska Stanoeva, Jasmina; Qazimi, Bujar; Daci, Armond (SAGE Publications, 2024)
Objective: Cydonia oblonga Mill . leaves ethanolic extract (CydOL-EE) has shown different cardioprotective effects. However, no previous studies investigated its direct effect on the vascular smooth muscle tone. Therefore, the study aimed to test the potential vasodilator activity of CydOL-EE in ex-vivo rat thoracic aorta preparations with an additional investigation of its mechanistic effects. Methods: CydOL-EE phytochemical profile was first investigated by HPLC-DAD-ESI-MS/MS and then tested for the vasorelaxation/vasoreactivity effects in rat aortic rings. The NO synthase inhibitor N(ω)-nitro-L-arginine methyl ester (L-NAME) and cyclic guanosine monophosphate inhibitor 1H-[1,2,4]Oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) were used to explore of the involvement of NO-dependent pathways. Results: Chromatographic analysis of CydOL-EE revealed the presence of six flavonols and seven hydroxycinnamic acids. Moreover, CydOL-EE showed a decrease in vasoreactivity caused by dose-dependent phenylephrine (PE) (Control, Emax = 104.29 ± 3.67 vs CydOL-EE, Emax = 70.73 ± 3.67, P < .0001) and a direct relaxing activity to precontraction with PE (Emax = 79.63 ± 3.67%). These responses were abolished during e-NOS inhibition, demonstrating that the mechanism of action was predominately controlled by the participation of an endothelium-dependent system. Conclusion: The results of our study show that CydO-EE demonstrates vasorelaxation and reduction of vasoreactivity through a NO-dependent pathway. These findings provide scientific evidence for further understanding of CydOL-EE use in the treatment of cardiovascular disease.